One-stage vs. three-stage repair in anorectal malformation with rectovestibular fistula - Omid Amanollahi; Saman Ketabchian (African Journal of Paediatric Surgery, 2016)
Background: Anorectal malformations (ARMs) disease is one of the congenital anomalies with an incidence of about 1 in 5000 neonate births, and treatment requires surgical intervention. Selecting the one- or three-step surgical procedure to treat the disease, especially in female neonates with rectovestibular fistula, is a subject of debate. This study aims to compare the advantages and disadvantages of these two methods. Materials and Methods: Forty female neonates with ARM and rectovestibular fistula between March 2011 and March 2013 were included in the study, and they were divided into two equal groups. Allocation of the first case was random, and all cases were then allocated alternatively (every other subject was assigned to a treatment group) until each group received 20 cases equally patients of study group underwent a one-stage posterior sagittal anorectoplasty (PSARP) and in control group patients underwent a three-stage operation (colostomy, PSARP, and closure of colostomy). The complications during and after the surgery were recorded in both groups, and the results were compared. Results: In the control group, only one case (5%) of wound infection and dehiscence was seen, whereas in the one-stage study group, six cases (30%) of wound infection and dehiscence were seen (P value = 0.046). However, regarding the incidence of other complications, such as iatrogenic vaginal injury as well as final recovery, no considerable differences were seen between the two groups. Conclusions: Despite more surgical site infections and dehiscence in the one-stage repair, but due to the numerous advantages compared to the three-stage method, which is more time-consuming, more costly, and causes more adverse effect on parents and children, performing the one-stage repair is recommended for this anomaly.